Distribución de amonitas del barremiano de la formación paja en el sector de villa de leyva (boyacá, colombia). bioestratigrafía (2000)
In the Barremian sedimentary succession of the Paja Formation in the Villa de Leyva area (Boyacá- Colombia), was found an ammonite fauna that allows to propose a biostratigraphy to correlate with the standard Mediterranean ammonite zones. The Early Barremian contains the Psilotissotia colombiana, Nicklesia pulchella and Pulchellia galeata zones. The Late Barremian Heinzia (Gerhardtia) veleziensis and Colchidites breistrofferi zones.  With the proposed biostratigraphy is possible a re-evaluation of Bürqls' ideas about the Barremian of Colombia, and to give precision to the vertical distribution of the collected ammonites in four sections near Villa de Leyva.  It is confirmed that the lower boundary of the Barremian and the Aptian in Colombia are not yetclearly defined.